DEVELOPMENT OF INNOVATIVE APPROACHES FOR NETWORK OPTIMIZATION USING GEOSPATIAL MULTI-COMPONENT SYSTEMS - Boyko, N. I.; Salanchii, T. O. (Radio Electronics, Computer Science, Control, 2025)
Context. Developing a geospatial multi-agent system for optimizing transportation networks is crucial for enhancing efficiency and reducing travel time. This involves employing optimization algorithms and simulating agent behavior within the network. Objective. The aim of this study is to develop a geospatial multi-agent system for optimizing transportation networks, focusing on improving network efficiency and minimizing travel time through the application of advanced optimization algorithms and agentbased modeling. Method. The proposed method for optimizing transportation networks combines foundational structure with advanced refinement in two stages: pre-processing and evolutionary strategy optimization. In the first stage, a Minimum Spanning Tree is constructed using Kruskal’s algorithm to establish the shortest, loop-free network that connects all key points, accounting for natural obstacles and existing routes. This provides a cost-effective and realistic baseline. The second stage refines the network through an evolutionary strategy, where agents representing MST variations are optimized using a fitness function balancing total path length, average node distances, and penalties for excessive edges. Optimization employs crossover to combine solutions and mutation to introduce diversity through edge modifications. Repeated over multiple epochs, this process incrementally improves the network, resulting in an optimized design that minimizes costs, enhances connectivity, and respects real-world constraints. Results. The results of applying the evolutionary strategy and minimum spanning tree methods were analyzed in detail. Comparing these methods to benchmarks like Tokyo’s railway network and the Slime Mold algorithm revealed the advantage of using the evolutionary approach in generating optimal paths. The findings emphasize the need for integrating advanced algorithms to further refine path optimization and network design. Conclusions. The research successfully developed a geospatial multi-agent system for optimizing transportation networks, achieving its objectives by addressing key challenges in transport network planning. A detailed analysis of existing solutions revealed the dynamic and complex nature of transportation systems and underscored the need for adaptability to environmental changes, such as new routes or obstacles. The proposed approach enhanced the minimum spanning tree with an evolutionary strategy, enabling flexibility and rapid adaptation. Results demonstrated the system’s effectiveness in planning optimal intercity transport networks. Future work could refine environmental assessments, improve route cost evaluations, expand metrics, define new performance criteria, and integrate neural network models to further enhance optimization capabilities, particularly for urban networks.